Introduction to the Apocrypha Jewish books in Christian bibles - Wills, Lawrence M. 1954- (New Haven, CT Yale University Press, 2021)
Frontmatter -- Contents -- Acknowledgments -- Note on Abbreviations -- Introduction -- ONE Novellas -- TWO Historical Texts -- THREE Wisdom Texts -- FOUR Apocalypses and Visionary Literature -- FIVE Psalms, Prayers, and Odes -- Conclusion -- Notes -- Bibliography -- Index of Subjects -- Index of Modern Authors -- Index of Ancient Sources
An ambitious introduction to the Apocrypha that encourages readers to reimagine what "canon" really means Challenging the way Christian and non-Christian readers think about the Apocrypha, this is an ambitious introduction to the deuterocanonical texts of the Christian Old Testaments. Lawrence Wills introduces these texts in their original Jewish environment while addressing the very different roles they had in various Christian canons. Though often relegated to a lesser role, a sort of "Bible-Lite," these texts deserve renewed attention, and this book shows how they hold more interest for both ancient and contemporary communities than previously thought
Mode of access: Internet via World Wide Web.
In English
Keywords: RELIGION / Biblical Commentary / Old Testament / Apocrypha & Deuterocanonical; RELIGION / Judaism / Sacred Writings